The Architectural Factor HMGB1 Is Involved in Genome Organization in the Human Malaria Parasite Plasmodium falciparum - Binbin Lu (American Society for Microbiology, 2021)
Malaria remains a major public health and economic burden currently. The mutually exclusive expression of the virulence genes is associated with the pathogenesis and immune evasion of human malaria parasites in the host.